Risk management of startups of innovative products - Taliat Bielialov (Journal of Risk and Financial Management, 2022)
The activation of the startup movement is one of the fundamental preconditions for the transition from innovation to a startup ecosystem, the development of which is impossible without special innovation structures that help startups promote innovative products on the market. The purpose of this article is to modernize the process of promoting innovative products on the market in the form of startups, taking into account the trends of the innovative development of the modern economy. The following methods are used in the article: situational and design approaches; methods of simulation and structural−functional modeling-to determine the potential market demand for innovative products and plan the process of their promotion to the market; and BPMN notation-to formalize the integration links between actors in the process of promoting innovative products on the market. As a result, a scheme for assessing the economic efficiency of innovative product market promotion process management was developed that sorts out several indicators at each stage of the innovation process, which allows one to increase the clarity and completeness of the promotion process management while reducing costs. The system of risk management of innovative products has been studied using the example of the promotion of the innovative startup Hideez Technology Ltd on the market in Europe and the USA. This has allowed the company to benefit economically from implementing the results, reaching USD 20,000. In conclusion, the sequence of actions for making management decisions during the implementation of the strategy for innovative product promotion process management was defined.
Keywords: 650; economic efficiency; innovation diffusion; innovation risk; management decision; startup